Crawling is Associated with Mental Rotation Ability by 9‐Month‐Old Infants. (19th May 2012) - Schwarzer, Gudrun; Freitag, Claudia; Buckel, Rebecca; Lofruthe, Annika
Abstract : The present experiment examined whether 9‐month‐old infants' mental rotation ability was related to their crawling ability. Forty‐eight 9‐month‐old infants were tested; half of them crawled for 7.1 weeks on average. Infants were habituated to a video of a simplified Shepard–Metzler object rotating back and forth through a 240° angle around the longitudinal axis of the object. Infants were tested with videos of the same object rotating through the previously unseen 120° angle and with the mirror image of that display. The results showed that the crawlers looked significantly longer at the mirror object than at the familiar object. The results support the interpretation that crawling experience is associated with 9‐month‐old infants' mental rotation ability.